High‐frequency and long‐term observations of eDNA from imperiled salmonids in a coastal stream: Temporal dynamics, relationships with environmental factors, and comparisons with conventional observations. Issue 4 (6th March 2022) - Searcy, Ryan T.; Boehm, Alexandria B.; Weinstock, Chloe; Preston, Christina M.; Jensen, Scott; Roman, Brent; Birch, James M.; Scholin, Christopher A.; Van Houtan, Kyle S.; Kiernan, Joseph D.; Yamahara, Kevan M.
Abstract: A greater understanding of eDNA behavior in the environment is needed before it can be employed for ecosystem monitoring applications. The objectives of this study were to use autonomous sampling to conduct long‐term, high‐frequency monitoring of the eDNA of native salmonid species in a Californian coastal stream, describe temporal variation of eDNA on multiple scales and identify environmental factors that drive this variation, and evaluate the ability of the eDNA datasets to detect rare species and represent organismal abundance. Using high‐throughput autonomous environmental sample processors (ESPs) and qPCR, we enumerated eDNA concentrations from 674 water samples collected at subdaily intervals over 360 days at a single site. We detected eDNA from two imperiled salmonids (coho salmon Oncorhynchus kisutch and steelhead/rainbow trout O . mykiss ) in most samples; O . kisutch eDNA was generally in lower concentration and more variable than O . mykiss eDNA. High‐frequency (i.e., subdaily and daily) variability in salmonid eDNA concentrations showed occasional patchiness (i.e., large differences between consecutive samples), while seasonal differences were observed consistent with the ecology of the species at this site. Salmonid eDNA concentrations were significantly associated with creek discharge, photoperiod, and whether the creek mouth was open or closed by a seasonal sandbar. The release of hatchery‐origin O . kisutch parr into the stream was associated with a significant increase in eDNA concentration for the remainder of the study. We compared eDNA signals with fish abundance data collected from traps located at the site. Fish were detected more often by eDNA than from trapping. Significant positive associations between fish abundance and eDNA concentrations were observed for O . mykiss ; however, no such associations were observed for O . kisutch . This study adds to our knowledge on the occurrence and behavior of fish eDNA in lotic systems and informs future biomonitoring efforts using automated sampling technology. Abstract : The objective of our study was to conduct high‐frequency autonomous sampling of salmonid eDNA in a coastal stream, elucidate the temporal patterns and environmental correlates of the eDNA signal, and compare the signal with a measure of abundance obtained from a fish trap collocated at the study site. We sampled one to three times per day for approximately one year, collecting nearly 700 samples. The eDNA signals showed high variability on short time scales and were aligned with expected salmonid seasonal trends in this ecosystem. Salmonid eDNA was significantly associated with creek discharge, photoperiod, and whether the creek mouth was open or closed by a seasonal sandbar. Comparing eDNA with fish counts from traps, we found that eDNA detected fish more often than traps but that eDNA concentrations were weakly or not at all correlated with fish abundance.